2011
DOI: 10.1080/13573322.2011.624594
|View full text |Cite
|
Sign up to set email alerts
|

Sport Education as a pedagogical application for ethical development in physical education and youth sport

Abstract: The purpose of this paper is to consider four pedagogical applications within the Sport Education model to examine the ways in which a young person can become a literate sports person and develop ethical behaviour through engagement in physical education and youth sport. Through a systematic review of the Sport Education research literature we present evidence to suggest that although notions such as inclusion, responsibility and ownership, personal and social development and social justice are part of the arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
24

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 40 publications
1
58
1
24
Order By: Relevance
“…The trend within research on Sport Education has highlighted its potential to be a highly inclusive pedagogical model (Hastie, Martinez, & Calderón 2011;Wallhead & O'Sullivan, 2005). Higher-skilled students are reported by their peers as being more supportive (Kinchin, 2001), and girls and less-skilful students feel they belong and that they can make valuable contributions to their teams (Harvey, Kirk, & O'Donovan, 2014;Hastie, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…The trend within research on Sport Education has highlighted its potential to be a highly inclusive pedagogical model (Hastie, Martinez, & Calderón 2011;Wallhead & O'Sullivan, 2005). Higher-skilled students are reported by their peers as being more supportive (Kinchin, 2001), and girls and less-skilful students feel they belong and that they can make valuable contributions to their teams (Harvey, Kirk, & O'Donovan, 2014;Hastie, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…The analysis shows the existence of various educational technologies for ethical development in such areas of learning as business (Seider et al, 2011), social work (Papouli, 2016), medicine (Melby et al, 2016;Vicentela et al, 2015) and nursing (Coleman & Dick, 2016), law and order (Xavier, 2016;Smith, 2015), physical culture (Santurio & Fernandez-Rio, 2014;Harvey et al, 2014), finance (Saat et al, 2014), IT-technologies and engineering (Bowden et al, 2015), archeology (Reid, 2014 ), journalism (Groshek & Conway, 2013) and many others. At the same time, the search for serious literary sources showed a shortage of research in educational technologies for ethical development among students of psychologists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this category there was some overlap with the SE literature. For example, Harvey, Kirk and O'Donovan (2014) explained that the SE model can be a context for character development if designed deliberately for this intention. They suggested that four pedagogical applications within SE be considered by PE teachers, youth sport practitioners and administrators to promote ethical development: 1. ethical contracts; 2. sports panels; 3. modified games; and 4. awards and rewards systems.…”
Section: Publication Title Findingsmentioning
confidence: 99%